2011
DOI: 10.3899/jrheum.110410
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Smoking on Disease Activity and Radiographic Progression in Early Rheumatoid Arthritis

Abstract: In patients with early RA, smoking was associated with earlier disease onset and the SE. Smoking was an independent factor of radiographic progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
19
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 14 publications
5
19
0
2
Order By: Relevance
“…A Swedish study reported that current smokers had a lower probability for a EULAR response or remission after 12 months in early RA patients 29 . However, a recent Spanish study with a similar setting did not show a significant effect of smoking 30 . Also, a study from CORRONA, in which the data structure was similar to ours, has not shown a significant effect of smoking cessation on disease activity 31 .…”
Section: Discussionmentioning
confidence: 75%
“…A Swedish study reported that current smokers had a lower probability for a EULAR response or remission after 12 months in early RA patients 29 . However, a recent Spanish study with a similar setting did not show a significant effect of smoking 30 . Also, a study from CORRONA, in which the data structure was similar to ours, has not shown a significant effect of smoking cessation on disease activity 31 .…”
Section: Discussionmentioning
confidence: 75%
“…Os resultados deste estudo contrastam com os do estudo prospectivo de Vesperini et al, que demonstrou recentemente menor risco de progressão em pacientes com AR inicial, 24 mas estão de acordo com os resultados de outros dois estudos, 25,26 enquanto que o estudo de Ruiz-Esquide et al demonstrou maior progressão radiográfica em tabagistas. 27 Portanto, a associação entre tabagismo e progressão radiográfica ainda é controversa.…”
Section: Discussionunclassified
“…Moreover, when comparing patients with a similar degree of radiographic joint destruction, women have worse scores for DAS28 and HAQ than men, possibly due to higher pain perception or an overestimate by men of their functional capacity [24]. Smoking is associated with a more severe disease and therefore probably more resistant to therapy [25, 26]. It also directly influences drug metabolism by inducing cytochrome P450 activity which was shown to impact other drug responses [27].…”
Section: Place Of Patient's Characteristics In Predicting Responsementioning
confidence: 99%